TINJAUAN MEDIKOLEGAL TERHADAPPERBUATAN GRATIFIKASI SPONSORSHIP OLEH PERUSAHAAN FARMASI - Trini Handayani (Jurnal MHKI, 2021)
Medicolegal is a medical service that refers to positive law. Doctors must comply with the Indonesian Medical Code of Ethics, Medical Discipline and Laws and Regulations related to medical services. One of the medicolegal violations is bribery gratification. The doctor gives a bribe gratuity after receiving sponsorship from a pharmaceutical company that is linked to the sales target of the pharmaceutical product. A gratification is a form of corruption, which is considered a bribe if there is a transactional reward (marketing fee) and is against the obligation. Pharmaceutical companies are not allowed to provide sales targets for their products related to the sponsorship. This sponsorship is not permitted in the form of money, but in the form of accommodation and registration of scientific activities in the context of improving knowledge or skills in medical action. The research method was carried out by interviewing and observing the pharmaceutical companies and practising doctors. As a result, there were frequent instances of graft cases indicated by bribes, both those offered by pharmaceutical companies and those requested by doctors. So far, there has been no sanction imposed on doctors who commit irregularities in a case of gratification.